Characterization of antiserum directed against form II ribulose 1,5-bisphosphate carboxylase from Rhodopseudomonas sphaeroides. - Gibson, J L (1977)
Antiserum directed against form II ribulose 1,5-bisphosphate carboxylase from Rhodopseudomonas sphaeroides showed no cross-reactivity towards the form I enzyme as evidenced by a lack of immunopreciptation. In addition, this antiserum failed to inhibit form I enzymatic activity.